Magnetron configurations dependent surface properties of SnO2 thin films deposited by sputtering process. (July 2020) - Gangwar, Amit Kumar; Godiwal, Rahul; Jaiswal, Jyoti; Baloria, Vishal; Pal, Prabir; Gupta, Govind; Singh, Preetam
Abstract: The effect of balanced magnetron (BM) and unbalanced magnetron (UBM) configurations, in RF sputtering process, on the surface properties of SnO2 thin films has been investigated. X-ray photoelectron spectroscopy (XPS) Sn3 d and O1 s core spectra reveal that the films deposited at RF power of 250 W under BM configuration consist of Sn 4+ oxidation states, while those deposited under UBM configuration consist of Sn 4+ and Sn 2+ oxidation states. This has been attributed to the migration of oxygen atoms from SnO2, resulting in the formation of Sn interstitial and oxygen vacancies. The contact angle (θ) recordings reveal that the UBM configuration results in more hydrophobic surface (140.6°) of SnO2 thin films than that under BM configuration (129.6°). Further, Atomic Force Microscopy (AFM) and Field Emission Scanning Electron Microscopy (FESEM) results indicate that the SnO2 thin films deposited under UBM configuration have better density with granular grains in comparison to that under BM configuration. The present studies establish the fact that magnetron configurations in sputtering process have significant impact on the surface properties of SnO2 thin films. Highlights: SnO2 films were deposited by RF sputtering process under BM and UBM configurations. Magnetron configuration is found to have strong impact on the surface properties of SnO2 films. Films deposited under UBM configuration at 250 W consists of Sn 4+ and Sn 2+ oxidation states. UBM sputtering process enables to deposit films with high hydrophobic surface than BM. UBM results in better density with granular grains in comparison to that using BM configuration.